Rancang Bangun Sistem Informasi Pelaporan Program Studi Teknologi Informasi Universitas Udayana - Indhiro Elsaday Nainggolan; Ni Wayan Emmy Rosiana Dewi; I Nyoman Prayana Trisna (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of technology has become an essential part of life and plays a significant role in simplifying various aspects, including the reporting process. People who wish to report an issue often hesitate or choose not to proceed because manual reporting is time-consuming, physically demanding, and prone to errors. Moreover, manual reporting is inefficient in determining which issues should be prioritized, and duplicate reports for the same problem are frequently encountered. These shortcomings make it difficult for report recipients to effectively process and act on the reports they receive. This research aims to address these challenges by developing a web-based digital reporting platform that enables users to submit reports easily, quickly, and efficiently. The features of the reporting system for the Information Technology Study Program at Udayana University were tested using the Blackbox Testing method to ensure that each function operates correctly and as expected. The system's feasibility was evaluated using the User Acceptance Testing method through a questionnaire designed to measure user satisfaction and convenience. Based on the test results, the system was deemed highly feasible, achieving a learnability score of 94.54%, efficiency of 94.09%, errors of 93.18%, satisfaction of 92.38%, and memorability of 94.54%. The reporting system for the Information Technology Study Program at Udayana University offers an effective, efficient, and innovative solution for digital reporting.